Revealed comparative advantage, international production chain and the evolving Asean-China trade linkages - Mendoza, Ronald U (Archīum Ateneo, 2015)
This paper reviews Chinese and ASEAN trade statistics to determine whether trade relations between the two regions are evolving to be competitive or complementary. The latest trend data and revealed comparative advantage indices show that China and ASEAN are experiencing growing bilateral trade while simultaneously competing in the production and export of major goods to similar trade destinations. The two regions, however, are becoming more engaged, highlighted by the increasing trade of intermediate goods and the slow but sure emergence of an integrated regional production and supply chain. As the ASEAN economies are diverse, dealing with the realities of an advancing ASEAN-China economic integration means each country enhances its competitive advantages, finds a niche in the regional production chain, and manages the competition with its neighbor. Strengthening the trade in parts and components is a way to improve trade complementarities between the regions.